Synthesis, Properties and Applications of Magnetic Ionic Liquids: An Overview - Rathod, Janhavi; Sherje, Atul P. (Current Green Chemistry, 2026)
Ionic fluids, known as magnetic ionic liquids, are paramagnetic at room temperature and do not require the addition of magnetic particles. Magnetic ionic liquids (MILs) exhibit unique and configurable physicochemical properties of ionic liquids as well as a significant response to external magnetic fields. MILs, as opposed to ferrofluids, are transparent, particle-free magnetic liquids. Since their discovery, major work has been done on finding the perfect applications of MILs, and since the last decade, it has been established that MILs could replace conventional, toxic solvents and become the suitable green solvents that can be used for a wide range of analytical experiments. MILs have been used extensively in analytical procedures like catalytic reactions and sample preparation, and a large amount of discoveries have been made in their applications for a variety of extraction procedures. Along with these, MILs have been used not only in analytical procedures but also in bioanalytical and biomedical procedures. MILs are being used in biological/biomedical applications because of their non-toxicity, ability to mould themselves according to the usage and generally easy-to-handle properties. This review aims to share these biomedical applications of MILs along with describing how the synthesis of MILs occurs and the important characteristics that these MILs should have.
Keywords: Ionic liquids